Sintesis Dan Pencirian Terbitan Baru Kalizarena Dan Penggunaannya Dalam Pengekstrakan Ion Logam. - Ahmad Tarmizi, Amirah Amalina (2008)

(untitled)
The alkylation between 25,27-bis(3-bromopropoxy)-26,28-dihydroxy-5,11,17-tetra(tertbutyl) calix[4]arene (CBr) and 4-hydroxybiphenyl-4’-carboxylic acid in the presence of potassium hydroxide and DMSO as the solvent yielded